Pengembangan Media Ular Tangga Berbantuan Kartu Komik Materi Bumi untuk Meningkatkan Hasil Belajar Siswa Kelas V - An Najmun Nuri Rokhim; Fitria Dwi Prasetyaningtyas (FONDATIA, 2026)
The limited development of game-based IPAS learning media integrated with visual literacy, particularly for earth-related content in elementary schools, forms the main basis of this study, as the abstract nature of earth topics requires concrete visualization to facilitate student understanding. The learning conditions in Grade V IPAS at SDN Podorejo 01 show limited use of interactive media with adequate visual elements, resulting in low student learning outcomes. This study aimed to develop and examine the feasibility and effectiveness of a snakes and ladders game medium supported by comic cards for the earth topic in the chapter “Mengenal Bumi Kita.” The study employed a Research and Development (R&D) approach with the ADDIE model, with product trials involving 6 students in a small-scale trial and 19 students in a large-scale trial. Data were collected through observation, interviews, questionnaires, as well as pretests and posttests, and were analyzed descriptively by calculating the feasibility percentage based on expert validation and the effectiveness response percentage, and quantitatively using paired-sample t-tests and N-Gain calculations. The results show that the developed medium obtained a very high feasibility rating from experts, with a percentage of 94%, and proved effective in improving student learning outcomes, as reflected in significant differences between pretest and posttest scores in both the small-scale trial (sig. = 0.010) and the large-scale trial (sig. = 0.000). The improvement in learning outcomes was further supported by N-Gain values of 0.6755 in the small-scale trial and 0.7192 in the large-scale trial. These findings indicate that the snakes and ladders game medium supported by comic cards contributes to enhancing the quality of IPAS learning and supports the development of innovative and contextual learning media in elementary schools.